Comercio potencial de servicios del Perú con el Asia Pacífico - Carazas, Pedro Miguel (2008)
Services account for 47% of global output and, as per several studies conducted, the liberalization of their trade brings more advantages than trade in goods. Despite of this fact, there has been little research on the subject, and the definition of services has remained controversial. Peru sticks to global trend, as services represent 65% of GDP and 75% of EAP. Moreover, the development of tertiary sector is essential to attain a hub position. This paper is aimed at identifying the potential trade in services with Asia Pacific, based on trade and liberalization indicators –this region accounts for nearly 18% of current world trade–. It considers the commercial behavior of Peru, as well as that of Chile and Colombia, which are regarded as competitors in their condition of «access platform» to the Andean sub region. It is concluded that there are many possibilities to intensify relations with Asia Pacific and policy recommendations that should be taken into account by the Peruvian foreign policy are provided.